2014
DOI: 10.1097/mpa.0b013e3182a85c21
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Cholinergic Stimulation as a Therapeutic Tool in Experimental Necrotizing Pancreatitis

Abstract: Stimulation of the cholinergic system is useful to attenuate damage in experimental acute pancreatitis. Not only prophylactic but also delayed application was effective in the present study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 44 publications
0
21
0
1
Order By: Relevance
“…However, there are studies which also suggest a protective 'anti inflammatory' role for nicotine in experimental AP. The postulated mechanisms by which nicotine exerts these effects include pathways mediated by the vagus and involving nicotinic receptors [93], cholinergic stimulation [94], modulating the immunoregulation of CD4 CD25 regulatory T cells [95]. It is likely that the cholinergic stimulation (via a(7)-nAChR) may result in the inhibition of the release of tumour necrosis factor (TNF) by macrophages [96].…”
Section: The Inflammatory Systemmentioning
confidence: 99%
“…However, there are studies which also suggest a protective 'anti inflammatory' role for nicotine in experimental AP. The postulated mechanisms by which nicotine exerts these effects include pathways mediated by the vagus and involving nicotinic receptors [93], cholinergic stimulation [94], modulating the immunoregulation of CD4 CD25 regulatory T cells [95]. It is likely that the cholinergic stimulation (via a(7)-nAChR) may result in the inhibition of the release of tumour necrosis factor (TNF) by macrophages [96].…”
Section: The Inflammatory Systemmentioning
confidence: 99%
“…They and others showed that electrical and pharmacological activation of the vagus inhibits many mostly innate immune responses ranging from cytokine responses to bacterial toxins as endotoxin, inflammation related to ileus, rheumatoid arthritis, colitis, hemorrhagic shock, myocardial ischemia/reperfusion, experimental pancreatitis and others [86][87][88][89][90]. The interaction of acetylcholine with nicotinic alpha7-ACh receptors (AChRs) on inflammatory cells plays an important role in the cholinergic anti-inflammatory pathway [85].…”
Section: Interplay Of Immune System and Nervous Systemmentioning
confidence: 98%
“…[79] In another investigation, both prophylactic and delayed-therapeutic treatment with nicotine diminished severity of acute experimental pancreatitis via stimulation of the cholinergic anti-inflammatory pathway. [80]…”
Section: Underlying Cellular Mechanisms Of Smoking-related Pancreatitismentioning
confidence: 99%